A photo-crosslinked bismuth oxide nanowire-fullerene-ferrocene composite negative electrode energy storage material
Through the photocrosslinked bismuth oxide nanowire-fullerene-ferrocene composite, the shortcomings of existing electrode materials in rapid reaction and cycle life are solved, and the supercapacitor material Bi2O3 with high specific capacitance and long cycle life are achieved. NW/C60/Fc, significantly improves specific capacitance and extends cycle life.
Patent Information
- Application Number
- CN202410986258.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-23
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-07-23
AI Technical Summary
The electrode materials of existing supercapacitors have shortcomings in rapid reaction, electron conduction performance and cycle life, especially the low capacity of fullerene and low conductivity of bismuth oxide, making it difficult to effectively integrate high conductivity and high specific capacitance. Characteristics.
Using photocrosslinked bismuth oxide nanowire-fullerene-ferrocene composite anode energy storage material, the photocrosslinking technology is used to form high specific capacitance and long Composite material with cycle life.
The specific capacitance is significantly improved and the cycle life extension is achieved. The specific capacitance of the composite Bi2O3 NW/C60/Fc reaches 1.89 times, and the attenuation is only 13.4% after 3,000 cycle life tests, indicating its excellent supercapacitance performance and service life.
Smart Images

Figure CN118737718B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy technology, in particular to a photo-crosslinked bismuth oxide nanowire-fullerene-ferrocene composite negative electrode energy storage material. Background Art
[0002] Supercapacitors have the characteristics of large specific capacity, fast charge and discharge capability, excellent cycle life, and environmental protection. According to the charge storage mechanism and electrode active materials, supercapacitors can be divided into double-layer capacitors, Faraday pseudocapacitors, and hybrid supercapacitors. Electrode materials are the core factor that determines the performance of supercapacitors. Commonly used electrode materials for supercapacitors can be roughly divided into three categories: carbon-based materials, metal oxides and hydroxides, and conductive polymer materials. Further development of new electrode materials based on fast response, excellent electronic conductivity, high cycle life, and high energy density is of great significance to the development of high-performance supercapacitors.
[0003] Fullerene C60 has a large free electron movement rate and high carrier mobility, and is often used as an electrode material with good electrochemical stability, but its capacitance as an energy storage material is low; bismuth oxide is a transition metal oxide with excellent electrical properties, and its specific capacitance is large, but its conductivity is relatively low; ferrocene is a metal organic complex with a π-bond sandwich structure, which has excellent redox properties. Based on this, a photo-crosslinked bismuth oxide nanowire-fullerene-ferrocene composite negative electrode energy storage material is proposed, which integrates the high conductivity of fullerene, the high specific capacitance of bismuth oxide and the excellent redox properties of ferrocene. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the deficiencies in the prior art, the present invention provides a photo-crosslinked bismuth oxide nanowire-fullerene-ferrocene composite negative electrode energy storage material to solve the above-mentioned problems.
[0006] (II) Technical solution
[0007] To achieve the above objectives, the present invention is implemented by the following technical scheme: a photo-crosslinked bismuth oxide nanowire-fullerene-ferrocene composite negative electrode energy storage material, the preparation steps of the crosslinked bismuth oxide nanowire-fullerene-ferrocene composite negative electrode energy storage material are as follows:
[0008] S1, adding 5.0 mg to 20.0 mg of a photoinitiator, 12.0 mg to 27.5 mg of ferrocenyl undecyl methacrylate and 10.0 mg to 27.5 mg of methyl methacrylate to 1 mL to 3 mL of a polyurethane prepolymer solution terminated with hydroxyethyl methacrylate, and performing ultrasonic dispersion to obtain a pretreated polyurethane prepolymer solution terminated with hydroxyethyl methacrylate;
[0009] S2. Use a micropipette to measure 73 μL-110 μL of the pre-treated hydroxyethyl methacrylate-terminated polyurethane prepolymer solution, drop it onto the nickel foam, dry it, and cure it with a 12 W ultraviolet lamp at a wavelength of 365 nm for 2 min-10 min to obtain the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc.
[0010] The present invention is further configured as follows: the size of the nickel foam in S2 is configured as 1 cm*4 cm.
[0011] The present invention is further configured as follows: the method for preparing the polyurethane prepolymer solution terminated with hydroxyethyl methacrylate in S1 comprises:
[0012] A1. Add 2.0g-4.0g of bismuth oxide nanowires, 25mg-50mg of fullerene alcohol, 25mg-50mg of 1,4-butanediol, 30mL-50mL of anhydrous butanone, 250mg-370mg of isophorone diisocyanate, and 1.0mg-4.0mg of dibutyltin dilaurate into a 100mL four-necked flask, stir mechanically, and react in an oil bath at 60-80°C for 3-6 hours to obtain a prepolymer;
[0013] A2. Cool down to 60-65°C, add 55mg-88mg of hydroxyethyl methacrylate, 1.0mg-5.0mg of inhibitor, and 2.0mg-4.0mg of catalyst, and continue the reaction at 60-65°C for 2-5 hours to obtain a polyurethane prepolymer solution terminated with hydroxyethyl methacrylate.
[0014] The present invention is further configured as follows: the prepolymer is prepared in A1 in an argon atmosphere.
[0015] The present invention is further configured as follows: the polymerization inhibitor in A2 is 4-methoxyphenol.
[0016] The present invention is further configured as follows: the catalyst in A2 is dibutyltin dilaurate.
[0017] The present invention is further configured as follows: the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc is used on the negative electrode of a supercapacitor.
[0018] (III) Beneficial effects
[0019] The present invention provides a photo-crosslinked bismuth oxide nanowire-fullerene-ferrocene composite negative electrode energy storage material. It has the following beneficial effects:
[0020] The present invention prepares a composite negative electrode energy storage material Bi2O3 NW / C60 / Fc by mixing homemade bismuth oxide nanowires and hydroxyl-modified fullerenes and reacting the mixture with isophorone diisocyanate to form a polyurethane prepolymer, capping the mixture with hydroxyethyl methacrylate, mixing the mixture with undecyl ferrocene methacrylate and methyl methacrylate, and coating the mixture on nickel foam for photo-crosslinking. The composite negative electrode energy storage material Bi2O3 NW / C60 / Fc is obtained, and the advantages of high conductivity of fullerene, high specific capacitance of bismuth oxide and excellent redox performance of ferrocene are integrated, so that the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc has higher specific capacitance and longer cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the structure of the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc in the present invention;
[0022] Figure 2 CV graphs of the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc and the commercial Bi2O3 electrode in the embodiment of the present invention;
[0023] Figure 3 The composite negative electrode energy storage material Bi2O3 NW / C60 / Fc in the embodiment of the present invention and the commercial Bi2O3 electrode at a current density of 1A -1 Constant current charge and discharge curve diagram below;
[0024] Figure 4 The composite negative electrode energy storage material Bi2O3 NW / C60 / Fc in the embodiment of the present invention is subjected to current densities of 1, 2, 5, 10 and 20A. -1 Constant current charge and discharge curve diagram when
[0025] Figure 5 Schematic diagram of the dependence of the specific capacitance of the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc on the current density in an embodiment of the present invention;
[0026] Figure 6 The electrochemical impedance spectra of the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc and the commercial Bi2O3 electrode in the embodiment of the present invention are shown;
[0027] Figure 7 Schematic diagram of the capacitance attenuation curve during the charge and discharge process of the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc in an embodiment of the present invention. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0029] See also Figure 1-7 , the embodiment of the present invention provides the following technical solution: the preparation steps of a photo-crosslinked bismuth oxide nanowire-fullerene-ferrocene composite negative electrode energy storage material are as follows:
[0030] S1. In an argon atmosphere, add 2.0 g to 4.0 g of bismuth oxide nanowire Bi2O3 NW, 25 mg to 50 mg of fullerene alcohol HO-C60, 25 mg to 50 mg of 1,4-butanediol BDO, 30 mL to 50 mL of anhydrous butanone, 250 mg to 370 mg of isophorone diisocyanate IPDI, and 1.0 mg to 4.0 mg of dibutyltin dilaurate T-12 into a 100 mL four-necked flask, stir mechanically, and react in an oil bath at 60-80 ° C for 3 to 6 hours to obtain a prepolymer;
[0031] S2, the prepolymer is cooled to 60-65°C, 55mg-88mg of hydroxyethyl methacrylate HEMA, 1.0mg-5.0mg of 4-methoxyphenol MEHQ, and 2.0mg-4.0mg of dibutyltin dilaurate T-12 are added, and the reaction is continued at 60-65°C for 2-5 hours to obtain a hydroxyethyl methacrylate-terminated polyurethane prepolymer solution HEMA-Bi2O3 NW / C60;
[0032] S3, adding 5.0 mg to 20.0 mg of photoinitiator HMPP, 12.0 mg to 27.5 mg of ferrocenyl undecyl methacrylate MAFc and 10.0 mg to 27.5 mg of methyl methacrylate MMA to 1 mL to 3 mL of hydroxyethyl methacrylate-terminated polyurethane prepolymer solution, and after ultrasonic dispersion, obtaining a pretreated hydroxyethyl methacrylate-terminated polyurethane prepolymer solution;
[0033] S4. Use a micropipette to measure 73 μL-110 μL of the pre-treated hydroxyethyl methacrylate-terminated polyurethane prepolymer solution, drop it onto the 1 cm*4 cm nickel foam, dry it, and cure it with a 12 W ultraviolet lamp with a wavelength of 365 nm for 2 min-10 min to obtain the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc.
[0034] It is further explained that the 73 μL-110 μL pre-treated hydroxyethyl methacrylate terminated polyurethane prepolymer solution in S4 contains 8.0-12.0 mg hydroxyethyl methacrylate terminated polyurethane prepolymer solution, 1.0-1.5 mg ferrocenyl undecyl methacrylate and 1.0-1.5 mg methyl methacrylate.
[0035] As a preferred solution, in order to study the electrochemical performance of the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc, a reference working electrode was introduced: a commercial Bi2O3 electrode. Cyclic voltammetry (CV) tests were performed on the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc and the commercial Bi2O3 electrode. The CV graph at a scan rate of 5 mV / s is shown in the attached figure. Figure 2 As shown, several redox peaks can be clearly observed in the CV curve, which means that both the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc and the commercial Bi2O3 electrode have typical redox properties. A small peak at about -0.66 V can be clearly observed in the CV curve, which may be caused by the oxidation of some residual bismuth during the oxidation process. It can also be seen that the redox peak current of the composite negative electrode energy storage material Bi2O3NW / C60 / Fc is significantly higher than that of the commercial Bi2O3 electrode, which is attributed to the unique nanostructure of the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc.
[0036] Furthermore, with Figure 2 The mass specific capacitance is calculated by the integral area in: The specific capacitance of commercial Bi2O3 electrodes is 245.7 F g -1 The mass specific capacitance of the composite negative electrode energy storage material Bi2O3NW / C60 / Fc is 464.8F g -1 , the specific capacitance is increased to 1.89 times.
[0037] As a preferred solution, the specific capacitance was further studied by constant current charge and discharge curves. -1 The constant current charge-discharge curves of the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc and the commercial Bi2O3 electrode are shown in the attached figure. Figure 3 As shown, it can be seen that the charge and discharge process is at a platform, which reflects the excellent pseudocapacitive properties of Bi2O3 NW / C60 / Fc.
[0038] To further illustrate, using the formula From the attached Figure 3 The discharge curve is calculated at a current density of 1A g -1 The specific capacitance of the commercial Bi2O3 electrode is 417.3 F g -1 The mass specific capacitance of the composite negative electrode energy storage material Bi2O3NW / C60 / Fc is 671.5F g -1 , the specific capacitance is increased to 1.61 times.
[0039] As a preferred solution, the dependence of the specific capacitance of the composite negative electrode energy storage material Bi2O3NW / C60 / Fc on the current density and the cycle life parameters are further studied through the constant current charge and discharge curve:
[0040] At current densities of 1, 2, 5, 10, and 20 A g -1 The constant current charge and discharge curves of the composite negative electrode energy storage material Bi2O3NW / C60 / Fc are shown in the attached figure. Figure 4 As shown, it can be seen that the charging and discharging process is at a platform, which reflects the excellent pseudocapacitive properties of the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc.
[0041] To further illustrate, using the formula From the attached Figure 4 The specific capacitance of the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc at different current densities was calculated from the discharge curve, as shown in the attached figure. Figure 5 As shown, the current density is 1, 2, 5, 10 and 20A g -1 When the specific capacitance is 671.5, 659.8, 646.0, 577.0 and 517.8 F g -1 It can be seen that with the increase of current density, the specific capacitance decreases slowly. -1 When the specific capacitance is as high as 671.5F g -1 , which indicates that Bi2O3 NW / C60 / Fc has superior supercapacitive performance.
[0042] As a preferred solution, the resistance of the composite negative electrode energy storage material Bi2O3NW / C60 / Fc and the commercial Bi2O3 electrode was compared by electrochemical impedance spectroscopy (EIS). The EIS curves in 6M KOH electrolyte are shown in the attached figure. Figure 6 As shown, it can be seen that the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc has a smaller semicircle radius in the high frequency region, and the smaller the radius, the smaller the internal resistance of the electrode, the faster the electron transfer efficiency, and thus the more efficient electrochemical performance.
[0043] In addition to fast charge and discharge, cycle life is another key parameter we studied. -1 The cycle life test of the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc was carried out under the following conditions. The results of 3000 times of rapid charge and discharge are shown in the attached figure. Figure 7 As shown, it was found that the specific capacitance decayed by 13.4% after 3000 cycles, indicating that it has an excellent service life.
[0044] As a detailed description, the electrochemical behavior of the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc and the reference electrode commercial Bi2O3 electrode was measured using CHI-660E, and the electrochemical measurement adopted a three-electrode system, 6MKOH solution or 0.5MNa2SO4 was used as the electrolyte, Bi2O3 NW / C60 / Fc and the commercial Bi2O3 electrode were used as the working electrode, and the Ag / AgCl / saturated KCl electrode and the platinum wire electrode were used as the reference electrode and the counter electrode, respectively. The preparation method of the commercial Bi2O3 electrode is as follows: weigh 8.0mg-12.0mg of commercial Bi2O3, add 30μL-50μL of glue and 1.0-1.5mg of acetylene black, mix into a paste, press it on a nickel foam sheet cut into 1cm*4cm, and bake at 80℃-120℃ for 2h-6h to obtain a reference working electrode, wherein the glue contains 0.3-0.5mg of polytetrafluoroethylene.
[0045] In summary, the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc prepared in this patent has the advantages of integrating the high conductivity of fullerene, the high specific capacitance of bismuth oxide and the excellent redox performance of ferrocene, and has higher specific capacitance and long cycle life. Specifically, at a current density of 1A g -1 The specific capacitance of the commercial Bi2O3 electrode is 417.3 F g -1 The mass specific capacitance of the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc is 671.5F g -1 , the specific capacitance increased by 61%; at 20.0A g -1 The cycle life test of the composite negative electrode energy storage material Bi2O3NW / C60 / Fc was carried out under the conditions. After 3000 cycles, the specific capacitance value decayed by 13.4%, indicating that it has a good cycle life.
Claims
1. A photo-crosslinked bismuth oxide nanowire-fullerene-ferrocene composite negative electrode energy storage material, characterized in that: The preparation steps of the cross-linked bismuth oxide nanowire-fullerene-ferrocene composite negative electrode energy storage material are as follows: S1, adding 5.0 mg to 20.0 mg of a photoinitiator, 12.0 mg to 27.5 mg of ferrocenyl undecyl methacrylate and 10.0 mg to 27.5 mg of methyl methacrylate to 1 mL to 3 mL of a polyurethane prepolymer solution terminated with hydroxyethyl methacrylate, and performing ultrasonic dispersion to obtain a pretreated polyurethane prepolymer solution terminated with hydroxyethyl methacrylate; S2. Use a micropipette to measure 73 μL-110 μL of the polyurethane prepolymer solution terminated with hydroxyethyl methacrylate, drop it onto the nickel foam, dry it, and cure it with a UV lamp with a power of 12 W and a wavelength of 365 nm for 2 min-10 min to obtain the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc; The preparation method of the polyurethane prepolymer solution terminated with hydroxyethyl methacrylate in S1 comprises: A1. Add 2.0g-4.0g of bismuth oxide nanowires, 25mg-50mg of fullerene alcohol, 25mg-50mg of 1,4-butanediol, 30mL-50mL of anhydrous butanone, 250mg-370mg of isophorone diisocyanate, and 1.0mg-4.0mg of dibutyltin dilaurate into a 100mL four-necked flask, stir mechanically, and react in an oil bath at 60-80°C for 3-6 hours to obtain a prepolymer; A2, cooling to 60-65°C, adding 55mg-88mg of hydroxyethyl methacrylate, 1.0mg-5.0mg of polymerization inhibitor, and 2.0mg-4.0mg of catalyst, and continuing the reaction at 60-65°C for 2-5 hours to obtain a polyurethane prepolymer solution terminated with hydroxyethyl methacrylate; Application of the composite negative electrode energy storage material Bi2O3 NW / C60 / Fc in the negative electrode of a supercapacitor.
2. The photo-crosslinked bismuth oxide nanowire-fullerene-ferrocene composite negative electrode energy storage material according to claim 1, characterized in that: The size of the nickel foam in S2 is set to 1cm*4cm.
3. The photo-crosslinked bismuth oxide nanowire-fullerene-ferrocene composite negative electrode energy storage material according to claim 1, characterized in that: In A1, the prepolymer was prepared in an argon atmosphere.
4. The photo-crosslinked bismuth oxide nanowire-fullerene-ferrocene composite negative electrode energy storage material according to claim 1, characterized in that: The polymerization inhibitor in A2 is 4-methoxyphenol.
5. The photo-crosslinked bismuth oxide nanowire-fullerene-ferrocene composite negative electrode energy storage material according to claim 1, characterized in that: The catalyst in A2 is dibutyltin dilaurate.
Citation Information
Patent Citations
Bismuth oxide nanowire-fullerene-ferrocene composite electrode capable of efficiently electrocatalytically degrading printing and dyeing wastewater
CN118405763A